The combination of dextran sulphate and polyvinyl alcohol prevents excess aggregation and promotes proliferation of pluripotent stem cells in suspension culture. (13th August 2021) - Tang, Xianglian; Wu, Haibin; Xie, Jinghe; Wang, Ning; Chen, Qicong; Zhong, Zhiyong; Qiu, Yaqi; Wang, Jue; Li, Xiajing; Situ, Ping; Lai, Liangxue; Zern, Mark A; et al.
Abstract: Objectives: For clinical applications of cell‐based therapies, a large quantity of human pluripotent stem cells (hPSCs) produced in standardized and scalable culture processes is required. Currently, microcarrier‐free suspension culture shows potential for large‐scale expansion of hPSCs; however, hPSCs tend to aggregate during culturing leading to a negative effect on cell yield. To overcome this problem, we developed a novel protocol to effectively control the sizes of cell aggregates and enhance the cell proliferation during the expansion of hPSCs in suspension. Materials and Methods: hPSCs were expanded in suspension culture supplemented with polyvinyl alcohol (PVA) and dextran sulphate (DS), and 3D suspension culture of hPSCs formed cell aggregates under static or dynamic conditions. The sizes of cell aggregates and the cell proliferation as well as the pluripotency of hPSCs after expansion were assessed using cell counting, size analysis, real‐time quantitative polymerase chain reaction, flow cytometry analysis, immunofluorescence staining, embryoid body formation, teratoma formation and transcriptome sequencing. Results: Our results demonstrated that the addition of DS alone effectively prevented hPSC aggregation, while the addition of PVA significantly enhanced hPSC proliferation. The combination of PVA and DS not only promoted cell proliferation of hPSCs but also produced uniform and size‐controlled cell aggregates. Moreover, hPSCs treated with PVA, or DS or a combination, maintained the pluripotency and were capable of differentiating into all three germ layers. mRNA‐seq analysis demonstrated that the combination of PVA and DS significantly promoted hPSC proliferation and prevented cell aggregation through improving energy metabolism‐related processes, regulating cell growth, cell proliferation and cell division, as well as reducing the adhesion among hPSC aggregates by affecting expression of genes related to cell adhesion. Conclusions: Our results represent a significant step towards developing a simple and robust approach for the expansion of hPSCs in large scale. Abstract : Polyvinyl alcohol (PVA) significantly promotes hPSC proliferation without compromising their pluripotency and differentiation capacity. The combination of PVA and dextran sulphate (DS) enhances cell proliferation and prevents cell aggregation of hPSCs in suspension culture. DS prevents cell aggregation of hPSCs by affecting expression of genes related to cell adhesion. PVA promotes hPSC proliferation by improving energy metabolism‐related processes.